2020
DOI: 10.1038/s41598-020-71670-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic neural activity recorded within breast tumors

Abstract: Nerve fibers are known to reside within malignant tumors and the greater the neuronal density the worse prognosis for the patient. Recent discoveries using tumor bearing animal models have eluded to the autonomic nervous system having a direct effect on tumor growth and metastasis. We report the first direct and chronic in vivo measurements of neural activity within tumors. Using a triple-negative mammary cancer mouse model and chronic neural interface techniques, we have recorded neural activity directly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…NGF has a neuroprotective effect on lidocaine-induced neurotoxicity (Zhao et al, 2017). In breast cancer, lidocaine may directly inhibit neural activity (McCallum et al, 2020). In this study, we observed that continuous intervention with lidocaine can significantly reduce the density of nerve fibers in mice bearing MBA-MB-231 or 4T1 tumors and down-regulate the expression levels of nerve-related proteins such as PGP9.5, NF, NGF, and Nnat.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…NGF has a neuroprotective effect on lidocaine-induced neurotoxicity (Zhao et al, 2017). In breast cancer, lidocaine may directly inhibit neural activity (McCallum et al, 2020). In this study, we observed that continuous intervention with lidocaine can significantly reduce the density of nerve fibers in mice bearing MBA-MB-231 or 4T1 tumors and down-regulate the expression levels of nerve-related proteins such as PGP9.5, NF, NGF, and Nnat.…”
Section: Discussionmentioning
confidence: 61%
“…Studies have shown that there are abundant nerve fibers and electrical activity in breast cancer tissues (McCallum et al, 2020), which are associated with the progression and metastasis of breast cancer (Huang et al, 2014). This may be associated with the ability of breast cancer cells to produce neurotrophic growth factors (Hondermarck, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, denervation causes regression of established breast cancer in ex vivo models [12], providing direct evidence that nerve supply is necessary for breast cancer growth. Consistently, chronic neural activity can be recorded within the tumour mass of mouse breast cancer models [13]. Of interest, sympathetic and parasympathetic nerves appear to have opposite effects on breast cancer growth [14]: sympathetic neurostimulation accelerates, whereas parasympathetic neurostimulation decelerates the progression of both human breast cancer xenografts and spontaneous breast cancer models in mice [14].…”
mentioning
confidence: 88%
“…However, it has also been observed that lidocaine (in clinically relevant doses) is able to block cancer-associated and prognostic relevant variants of voltage-activated sodium channels like Nav1.5 [ 111 ]. Interestingly, a recent animal study detected chronic electric activity in solid breast tumor masses in mice [ 112 ]. This activity is supposedly of neuronal origin, as it has a connection to the parasympathetic nervous system, which disrupts on injection of lidocaine and chemical sympathectomy [ 112 ].…”
Section: Recent and Current Datamentioning
confidence: 99%
“…Interestingly, a recent animal study detected chronic electric activity in solid breast tumor masses in mice [ 112 ]. This activity is supposedly of neuronal origin, as it has a connection to the parasympathetic nervous system, which disrupts on injection of lidocaine and chemical sympathectomy [ 112 ]. With these neuronal networks, systemically administered lidocaine could, therefore, have a new target in its first described mechanism of action, thus disrupting the neuronal membrane potential and neural activity during tumor growth and metastasis.…”
Section: Recent and Current Datamentioning
confidence: 99%